STRATEGI KEPALA SEKOLAH DALAM MENGEMBANGKAN RELIGIOUS CULTURE MELALUI MANAJEMEN PEMBIASAAN DIRI BERDOA BERSAMA SEBELUM BELAJAR DI SMP NEGERI 5 MEDAN TAHUN AJARAN 2019/2020 - Syahbilal Syahbilal (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2022)
The purpose of school action research is to find out the principal's strategy in developing religious culture at SMP Negeri 5 Medan through the management of the habit of praying together before studying. This school action research was carried out at SMP Negeri 5 Medan, the method used in this study was descriptive qualitative, the research data sources were the principal, teachers of Islamic religious subjects at SMP Negeri 5 Medan, the data collection methods were observation sheets, interviews, documentation, literature study, data analysis techniques namely: data collection, data reduction, data display. Based on the discussion described earlier, the authors can draw conclusions, namely first, the application of Religious Culture in Medan 5 Public Middle School can be seen from the aspects of the activities carried out, namely: praying together before studying, carrying out midday prayers in congregation at school, commemorating Islamic holidays , Infaq every Friday addressed to the mosque, and the application of smiles, greetings, greetings. Second, the principal's strategy in developing a religious culture at SMP Negeri 5 Medan through the management of the habit of praying together before studying at school is carried out by making plans, setting an example, participating in every activity, habituating, evaluating. Third, the supporting factors for school principals in developing Religious Culture at SMP Negeri 5 Medan are good coordination between the teacher council, the community, and parents if there are students who do not carry out the existing programs. The teacher is a factor that has a very important role in the realization of quality and successful Religious Culture activities.